1.
(sin3A+sinA) / (cos3A+cosA) =
= (2·sin((3A+A)/2)·cos((3A-A)/2)) / (2·cos((3A+A)/2)·cos((3A-A)/2)) =
= (2·sin2A·cosA) / (2·cos2A·cosA) =
= (2·sin2A) / (2·cos2A) =
= (2·sin2A·cos2A) / (2·cos2A·cos2A) =
= (sin4A) / (2·cos²2A) =
= (sin4A) / (2·cos²2A) = (sin4A) / (1+cos4A)
2.
4·cos(A/3)·cos(A/4)·cos(A/6) =
= 4·cos(A/4)·(cos(A/3)·cos(A/6)) =
= 4·cos(A/4)·(1/2)·(cos(A/3+A/6)+cos(A/3-A/6)) =
= 2·cos(A/4)·(cos(A/2)+cos(A/6)) =
= 2·cos(A/4)·cos(A/2)+2·cos(A/4)·cos(A/6) =
= 2·(1/2)·(cos(A/4+A/2)+cos(A/4-A/2)) +
+ 2·(1/2)·(cos(A/4+A/6)+cos(A/4-A/6)) =
= cos(3A/4)+cos(-A/4)+cos(5A/12)+cos(A/12) =
= cos(3A/4)+cos(A/4)+cos(5A/12)+cos(A/12)
x+3=x^2+2x-3 x^2+2x-3>0
x^2+2x-3-x-3=0 x^2+2x-3=0
x^2+x-6=0 x₁+x₂=-2
x₁+x₂=-1 x₁*x₂=-3
x₁*x₂=-6 x₁=-3; x₂=1 => x<-3; x>1
x₁=-3 - не входит в ОДЗ x>1
x₂=2
x=2
log_2(2x-1)-2=log_2(x+2)-log_2(x+1) ОДЗ: 2x-1>0 => x>0.5
log_2(2x-1)-log_2(4)= log_2(x+2)-log_2(x+1) x+2>0 => x>-2 log_2((2x-1)/4)=log((x+2)/(x+1)) x+1>0 => x>-1 (2x-1)/4=(x+2)/(x+1) x>0.5
(2x-1)(x+1)=4(x+2)
2x^2+x-1-4x-8=0
2x^2-3x-9=0
D=(-3)^2-4*2*(-9)=81 √81=9
x₁=3
x₂=-1.5 - не входит в ОДЗ
х=3
log_5(2x^2-x)/log_4(2x+2)=0 ОДЗ: 2x^2-x>0 => x>0.5
log(4)log(2x^2-2)/log(5)log(2x+2)=0 2x+2>0 => x>-1
log(2x^2-x)/log(2x+2)=0
log(2x^2-x)=0
log(2x+2)≠0
2x^2-x=1
2x^2-x-1=0
D=9
x₁=1
x₂=-0.5 - не входит в ОДЗ
x=1
log_2x(x^2+x-2)=1 ОДЗ: 2x>0 => x>0
log_2x(x^2+x-2)=log_2x(2x) x^2+x-2>0
x^2+x-2=2x x^2+x-2=0
x^2-x-2=0 x₁+x₂=-1
x₁+x₂=1 x₁*x₂=-2
x₁*x₂=-2 x₁=-2; x₂=1
x₁=2 x>1
x₂=-1 - не входит в ОДЗ
x=2